2012
DOI: 10.1021/ac300544s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Structural Building Blocks in Heavy Petroleum Systems by Collision-Induced Dissociation Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Collision-induced dissociation Fourier Transform ion cyclotron resonance mass spectrometry (CID-FTICR MS) was developed to determine structural building blocks in heavy petroleum systems. Model compounds with both single core and multicore configurations were synthesized to study the fragmentation pattern and response factors in the CID reactions. Dealkylation is found to be the most prevalent reaction pathway in the CID. Single core molecules exhibit primarily molecular weight reduction with no change in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…Additionally, the loss of further fragments that differ in mass by multiples of 14 Da is observed. Following Qian et al, this could correspond to the loss of varying numbers of methylene units along the side chain, as depicted in Figure . Considering that the individual sulfur compounds present in the sample are likely to have an aromatic core structure, such as benzothiophene (BT), dibenzothiophene (DBT) or benzonaphthothiophene (BNT), among others, this would lead to the conclusion that besides the terminal CH 3 groups the side chains are cleaved at arbitrary positions with the loss of varying numbers of methylene units from fragment to fragment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the loss of further fragments that differ in mass by multiples of 14 Da is observed. Following Qian et al, this could correspond to the loss of varying numbers of methylene units along the side chain, as depicted in Figure . Considering that the individual sulfur compounds present in the sample are likely to have an aromatic core structure, such as benzothiophene (BT), dibenzothiophene (DBT) or benzonaphthothiophene (BNT), among others, this would lead to the conclusion that besides the terminal CH 3 groups the side chains are cleaved at arbitrary positions with the loss of varying numbers of methylene units from fragment to fragment.…”
Section: Resultsmentioning
confidence: 99%
“…Some of those reports are the result of CID studies of synthesized compounds, albeit produced using synthetic methods that lead to a mixture of isomers. These might result in different fragmentation patterns and thus invalidate the interpretation of fragmentation mechanisms, as single fragments cannot be attributed to single isomers from the mixture …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis revealed that both island and archipelago-type molecules were present in each aromatic ring fractions. Qian et al determined the typical aromatic building blocks contained in heavy petroleum fractions by FT-ICR MS with collision induced dissociation (CID) 12) . Their studies provided basic knowledge about the fragmentation of both island and archipelago-type molecules in CID analysis, indicating that the vacuum residue (VR) contains both island and archipelago-type structures.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Characterization of sulfur compounds has been an important research topic in the petroleum community; 7−15 however, this issue has been challenging due to the complex hydrocarbon matrix and the inherent molecular complexity of sulfur compounds in heavy oils. 16,17 Separation of sulfur compounds from petroleum is critical for their multifaceted detailed characterization.…”
mentioning
confidence: 99%